Using MATLAB to model and simulate a photovoltaic system to produce hydrogen. (1st April 2019) - Ismail, Tamer M.; Ramzy, Khaled; Elnaghi, Basem E.; Abelwhab, M.N.; El-Salam, M. Abd
Highlights: Hydrogen production method from direct coupling between the PVG and PEM was studied. The experimental work was done for the month of March in Suez city, Egypt. The temperature has a significant influence on the power of the PV generator. Modelling of the solar hydrogen production using the PV-PEM direct coupling was studied. Abstract: Energy is currently the basis for development in different areas worldwide. Traditional sources of energy such as coal, oil, and nuclear energy have serious repercussions on the environment and are non-renewable energies. Therefore, renewable energy, like solar, wind, and marine energy, are alternatives. Egypt is considered an important country that has climatic averages allowing the exploitation of renewable energy. Solar energy is available in Egypt, especially in Upper Egypt, throughout the year. Different models have been created to estimate and predict the global solar radiation intensity due to the shortage of measuring stations. This study presents a mathematical model to estimate and predict the global solar radiation intensity in Egypt. This model is compared and validated against published measurements of global solar radiation intensity. Furthermore, this study introduces a hybrid system used to produce hydrogen (photovoltaic generator–PEM electrolyzer). Modelling and simulating methods is done by running a flowchart in MATLAB to minimize the losses in the system and increase the quantity of hydrogen produced. The simulation includes the global solar radiation estimation and the photovoltaic generator–PEM electrolyzer. The experiment was conducted in March in Suez city, Egypt. The results obtained showed that the model of global solar radiation gives a good prediction for estimating the intensity of global solar radiation in Egypt. Furthermore, they concluded that there is a significant improvement in system performance that signifies an increase in the volume of hydrogen produced by the system. The whole model is simulated, and the simulation results fit the experimental data very well. The electrolyzer is powered by a PV panel and is modelled, sized, and experimentally validated.